Intensive systolic blood pressure control and incident chronic kidney disease in people with and without diabetes mellitus: secondary analyses of two randomised controlled trials. Issue 7 (July 2018) - Beddhu, Srinivasan; Greene, Tom; Boucher, Robert; Cushman, William C; Wei, Guo; Stoddard, Gregory; Ix, Joachim H; Chonchol, Michel; Kramer, Holly; Cheung, Alfred K; Kimmel, Paul L; Whelton, Paul K; et al.
Summary: Background: Guidelines, including the 2017 American College of Cardiology and American Heart Association blood pressure guideline, recommend tighter control of systolic blood pressure in people with type 2 diabetes. However, it is unclear whether intensive lowering of systolic blood pressure increases the incidence of chronic kidney disease in this population. We aimed to compare the effects of intensive systolic blood pressure control on incident chronic kidney disease in people with and without type 2 diabetes. Methods: The Systolic Blood Pressure Intervention Trial (SPRINT) tested the effects of a systolic blood pressure goal of less than 120 mm Hg (intensive intervention) versus a goal of less than 140 mm Hg (standard intervention) in people without diabetes. The Action to Control Cardiovascular Risk in Diabetes (ACCORD) blood pressure trial tested a similar systolic blood pressure intervention in people with type 2 diabetes. Our study is a secondary analysis of limited access datasets from SPRINT and the ACCORD trial obtained from the National Institutes of Health. In participants without chronic kidney disease at baseline (n=4311 in the ACCORD trial; n=6715 in SPRINT), we related systolic blood pressure interventions (intensive vs standard) to incident chronic kidney disease (defined as >30% decrease in estimated glomerular filtration rate [eGFR] to <60 mL/min per 1·73 m 2 ). These trials are registered withClinicalTrials.gov, numbersNCT01206062 (SPRINT) andNCT00000620 (ACCORD trial). Findings: The average difference in systolic blood pressure between intensive and standard interventions was 13·9 mm Hg (95% CI 13·4–14·4) in the ACCORD trial and 15·2 mm Hg (14·8–15·6) in SPRINT. At 3 years, the cumulative incidence of chronic kidney disease in the ACCORD trial was 10·0% (95% CI 8·8–11·4) with the intensive intervention and 4·1% (3·3–5·1) with the standard intervention (absolute risk difference 5·9%, 95% CI 4·3–7·5). Corresponding values in SPRINT were 3·5% (95% CI 2·9–4·2) and 1·0% (0·7–1·4; absolute risk difference 2·5%, 95% CI 1·8–3·2). The absolute risk difference was significantly higher in the ACCORD trial than in SPRINT (p=0·0001 for interaction). Interpretation: Intensive lowering of systolic blood pressure increased the risk of incident chronic kidney disease in people with and without type 2 diabetes. However, the absolute risk of incident chronic kidney disease was higher in people with type 2 diabetes. Our findings suggest the need for vigilance in monitoring kidney function during intensive antihypertensive drug treatment, particularly in adults with diabetes. Long-term studies are needed to understand the clinical implications of antihypertensive treatment-related reductions in eGFR. Funding: National Institutes of Health.